Influence of COVID-19 on the Perception of Academic Self-Efficacy, State Anxiety, and Trait Anxiety in College Students - Alemany-Arrebola, Inmaculada; Rojas-Ruiz, Gloria; Granda-Vera, Juan; Mingorance-Estrada, Ángel Custodio (Frontiers in Psychology, 2020)
The worldwide pandemic situation caused by coronavirus disease 2019 (COVID-19) has led to a state of confinement of the population, which has caused, following consulted research, an increase in stress. Faced with this situation, the Spanish university not only had to adapt to the changes derived from the causes of the pandemic but also had to face a new methodological model—e-learning teaching—for which not all teachers and students were prepared. This could cause an increase in stress due to the uncertainty caused by this time of change. This research analyzes the relationship between perceived self-efficacy in the confinement period and the level of trait anxiety (TA) and state anxiety (SA) during COVID-19. Four hundred twenty-seven students from the University of Granada (Spain) participated in this study. The adaptation of two scales that measure perceived academic self-efficacy and anxiety (TA and SA) has been applied. The results indicated that there was an inversely proportional relationship between anxiety and self-efficacy; men showed the highest perception of self-efficacy, while women had higher scores in TA and SA; the latter was accentuated in cases when a relative died. To conclude, students who show a higher level of anxiety (TA and SA) express more negative emotions and also perceive themselves with less academic self-efficacy. Therefore, a stressful situation (pandemic and confinement) together with a critical event (illness and death of a relative/friend due to COVID-19) increases anxiety levels and influences the perception of academic self-efficacy.